Plantio adensado e diverso e sua relação sobre o comportamento de espécies florestais - Costa, Danilo Ribeiro da (Universidade Federal de São Carlos, 2020)
Restoration models with high density of individuals promote early inter- and intraspecific competition processes, influencing growth relationships. Our study aimed to analyze how the species perform in relation to growth, mortality, and competition in dense and in high diversity conditions and its influence in their ecological classification. An eight-year-old dense (3 to 4 plants.m-²) and diverse (142 species) restoration area was analyzed, obtaining height, diameter, and survival data of 701 individuals of 51 species. In circular plots (7.069 m²) competition rates were determined based on the height and diameter of each plant in relation to its neighbors. Analysis of multiple linear regressions, principal components and network allowed to evaluate the relationships between variables and species. The competition indexes made it possible to characterize the differences in species response according to their neighbors. The successional classification of pioneers and non-pioneers was the one that most contributed to express the competitive relationship between species. Bifurcated individuals had greater competitive potential when subjected to high species richness and showed greater competitive potential by height. Species such as Mimosa bimucronata, Guazuma ulmifolia and Croton urucurana demonstrated highly competitive capacity inhibiting their neighborhood. Although they enable the initial vegetation structure, we recommended their use in low density and frequency in ecological restoration.
Dense and diverse planting, and its relationship on the behavior of forest species
Keywords: Restauração Florestal; Índices de Competição Individuais; Sucessão Ecológica; Forest Restoration; Individual Competition Indices; Ecological Succession; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; ENGENHARIAS